2007
DOI: 10.1007/s10194-007-0413-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler measurements in migraine and nitroglycerin headache

Abstract: The objective of this study was to examine the cerebral circulation during spontaneous migraine attacks and to compare changes to an experimental headache model induced by nitroglycerin (NTG) infusion. This prospective study was carried out in a tertiary care hospital on migraineurs with or without aura. Healthy volunteers served as controls. There were no interventions. Flow velocity (FV) and pulsatility index (PI) were measured in migraineurs between and during headache attacks. In controls, FV and PI of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…About 14 studies reported use of TCD measurements at 2 MHz pulsed ultrasound, but the depth variations as well as using the same parts of the temporal window or meato‐orbital‐line and other inter‐operator methodological discrepancies cannot be ruled out. The remaining three studies did not report technical TCD information . The included studies thus represent a very heterogeneous group rendering quantitative data synthesizing inappropriate for this review.…”
Section: Discussionmentioning
confidence: 99%
“…About 14 studies reported use of TCD measurements at 2 MHz pulsed ultrasound, but the depth variations as well as using the same parts of the temporal window or meato‐orbital‐line and other inter‐operator methodological discrepancies cannot be ruled out. The remaining three studies did not report technical TCD information . The included studies thus represent a very heterogeneous group rendering quantitative data synthesizing inappropriate for this review.…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of studies using mostly indirect measurements of vascular diameter have provided conflicting results. (1317) A recent 3-Tesla magnetic resonance angiography study has questioned the importance of the cerebral vasculature in the pathophysiology of migraine. (18) Investigations of twenty migraine without aura attacks provoked by nitroglycerin identified no significant changes in cerebral artery diameters or cerebral blood flow during migraine.…”
Section: Imaging Migrainementioning
confidence: 99%
“…In order to obtain novel information on intracranial vascular processes during headache, a variety of methods have been employed, ranging from transcranial Doppler (TCD) [8] to high resolution magnetic resonance angiography (MRA) [6]. In animal models, closed cranial window with intravital epifluorescence microscopy is one of the best established methods since the end of 90s [9].…”
Section: Introductionmentioning
confidence: 99%